2017
DOI: 10.1016/j.bcab.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Potential of the filamentous fungus Aspergillus niger AN 400 to degrade Atrazine in wastewaters

Abstract: This research aims to evaluate the ability of the fungal specie Aspergillus niger AN 400 to metabolize atrazine (ATZ) in model wastewaters, as most of the research with this worldwide used herbicide is focused on bacteria and on soil bioremediation. Firstly, the tolerance of A. niger for ATZ was evaluated in petri dishes. A. niger growth in all the tested ATZ concentrations, up to 30 mg L −1. Biodegradation of ATZ was then conducted in batch reactors of 3 L, with dispersed fungal biomass. Reactors were operate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 25 publications
0
13
1
Order By: Relevance
“…with the flow rate ranging from 10 to 40 mL•h -1 and the HRT from 24 to 100 h. Results also showed that the continuous packed bed bioreactor was able to regains its performance quickly after the perturbation in the flow rate. The potential of the same fungus Aspergillus niger to degrade continuously an herbicide, atrazine, in wastewater was evaluated by Marinho et al (2017).…”
Section: Pesticidesmentioning
confidence: 99%
“…with the flow rate ranging from 10 to 40 mL•h -1 and the HRT from 24 to 100 h. Results also showed that the continuous packed bed bioreactor was able to regains its performance quickly after the perturbation in the flow rate. The potential of the same fungus Aspergillus niger to degrade continuously an herbicide, atrazine, in wastewater was evaluated by Marinho et al (2017).…”
Section: Pesticidesmentioning
confidence: 99%
“…The proteome analysis indicated that, in this case, extracellular hydrolases and peroxidases were overexpressed in the extracellular environment. Marinho et al [29] found that atrazine degradation by Aspergillus niger in batch reactors containing wastewater and 30 mg L − 1 of the herbicide reached 40% after 8 days. The biodegradation rose up to 72% when the mixture was supplemented with 3 g L − 1 of glucose, allowing more extensive biomass development.…”
Section: Discussionmentioning
confidence: 99%
“…The proteome analysis indicated that, in this case, extracellular hydrolases and peroxidases were overexpressed in the extracellular environment. Marinho et al [29] found that atrazine degradation by Aspergillus niger in batch reactors containing wastewater and 30 mg L -1 of the herbicide reached 40% after 8 days. The biodegradation raised up to 72% when the mixture was supplemented with 3 g L -1 of glucose, allowing more extensive biomass development.…”
Section: Discussionmentioning
confidence: 99%